1995
DOI: 10.1159/000213661
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor, Natural Killer Activity and Other Measures of Immune Function and Inflammation in Elderly Men with Heart Failure

Abstract: Objective: To determine the status of tumor necrosis factor (TNF) and other measures of immunity and inflammation in chronic heart failure (CHF) in the elderly. Design: Comparative survey study of subjects with heart failure and age-matched controls. Settings: University affiliated tertiary care VA Medical Center, Heart Failure Clinic. Patients: Twenty men with New York Class II and III heart failure and 17 age-matched controls. Interventions: None. Main outcome measure: Levels of lymphocyte mitogenesis, TNF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…TNF-was measured by ELISA in 16 patients, and all had at least one sample with no detectable TNF-. Other studies have failed to show a significant increase in TNFconcentration in CCF [12], possibly due to be the patients being relatively old. In the present study, only two patients were under 60 years of age.…”
Section: Discussionmentioning
confidence: 88%
“…TNF-was measured by ELISA in 16 patients, and all had at least one sample with no detectable TNF-. Other studies have failed to show a significant increase in TNFconcentration in CCF [12], possibly due to be the patients being relatively old. In the present study, only two patients were under 60 years of age.…”
Section: Discussionmentioning
confidence: 88%
“…Several studies have shown that CHF is associated with activation of the immune system 7,8,18–25 . However, whether this immune activation is responsible for, or a result of, impaired cardiac function is to a large degree unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observed elevated levels of this cytokine only in 6.9% of patients; this result is similar to that reported by van Riemsdijk-van Overbeeke et al 31 , who failed to detect serum levels of free TNFα in HF patients notwithstanding their finding of elevated levels of TNFα soluble receptors with increased binding capacity, which explained the low TNFα bioavailability. Additionally, no change in the levels of this cytokine when compared to control healthy individuals was reported in two other studies done in patients with mild or moderate heart failure [32][33] .…”
Section: Discussionmentioning
confidence: 75%